PENGARUH NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR ILMU PEGETAHUAN SOSIAL KELAS V SEKOLAH DASAR - Kurniati, Kurniati; Halidjah, Siti; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis research aims to determine the effect of the numbered head together in the learning outcomes of Social Sciences at grade V SDN 38 Pontianak Utara. The method used is an experimental method. This research, using the Quasi Experimental Design with the Nonequivalent Control Group Design. This sample in this research is grade V B (experimental class) selected by purposive sampling. Data collection techniques used are measurement techniques. The data collection tool used is a test. Result on the data analysis, the average post-test experimental class were 77.68 and the post-test control class was 69.96, obtained by tcount 3.24 and ttable (Î± = 5% and dk = 22 + 24 - 2 = 44) amounting to 1.68, because tcount> ttable, then Ha is accepted. So, it can be concluded that there is an effect of the numbered head together in the learning outcomes of Social Sciences at grade V SDN 38 Pontianak Utara.Â  The effect size (ES) calculation was obtained 0.81 (high criteria). It meant that the numbered head together gives a high influence in the learning outcomes of Social Sciences at grade V SDN 38 Pontianak Utara.Keywords:Numbered Head Together, Learning Outcomes